Study guides

☆☆

Q: What is 3x - 14x?

Write your answer...

Submit

Still have questions?

Related questions

3x/7 + 5y/14x = 3x*2x/(7*2x) + 5y/14x = (6x2 + 5y)/14x

3x-7 = 14x-29 29-7 = 14x-3x 22 = 11x x = 2 Hope that helps!!;)

3x^2 -14x +15 = (3x-5)(x-3)

3x2 -14x -24 can be factored as (3x + 4)(x - 6).

(14x-2y)+(7x-3y)+(-3x) = 14x-2y+7x-3y-3x =(14+7-3)x-(2+3)y =18x-5y

57

(x - 4)(3x - 2)

5x^2 + 14x - 3x^2 - 9 = 2x^2 + 14x - 9

(3x + 1)(x - 5)

5x+8x+3x-2x = 14x

6x2 + 14x -12 = (3x - 2) (2x + 6). There they are.

if i read this right it's -14x

2x(x2 + 3x - 7)

2(2x - 5)(3x + 4)

The product of (3x-1)(x+5) = 3x^2 +14x -5 by multiply out the brackets

(3x - 2)(2x + 6) or 2(3x - 2)(x + 3)

yes, and it is 14x

It is (3x-1)(x+5) when factored

Just one.17x - 8 = 3x + 16Subtract 3x from each side:14x - 8 = 16Add 8 to each side:14x = 24Divide each side by 14:x = 24/14 = 12/7 = 15/7

(3x+1)(2x+4) = 6x2+4+2x+12x = 6x2+14x+4

6x2 - 13x - 63 = 6x2 + 14x - 27x - 63 = 2x(3x + 7) - 9(3x + 7) = (3x + 7)(2x - 9)

I assume the question is to factor this problem? 6x2 + 14x - 12 can be factored to give (6x - 4)(x + 3) and then factor out a 2 to give 2(3x - 2)(x + 3) OR you could've factored with (3x - 2)(2x + 6), but the final answer would still be the same. 2(3x - 2)(x + 3)

x + (3x - 2) = 14x + 3x - 2 = 144x - 2 = 144x = 16x = 4

10x^3 plus 14x^2-4x+16

y=-2/3x with any y-intercept except -2.